(3EaQGO GdebGd aj CeQ GdXdGds - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3GdcdGe ai GdEOQGc GdHUQi hcjajI GdMGd ai GdeNQhW GdcGFf Hjf GdHUQ hGdeHUQ s
(3BNQgG (B:s
(3hCXf gPG GdbOQ ai JYQa CehQ GdEXdGd cGajkG hYdi JUMjM GdChbGJ ai GdBdGJ HGdEXdGd hGddg JYGdi Gdehab CdN s
(3Cdag ddTjN CHj GdMSf eSGaQ Hf GdMSjfs
(3hQJHg Ydi KdGKjf HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
Keywords: (3GdQjGVjGJs